Cellulolytic enzyme-producing thermophilic Actinobacteria isolated from the soil of Cisolok Geysers, West Java, Indonesia - PUTRI PRATIWI SETYANINGSIH; FITRIA NINGSIH; MAZYTHA KINANTI RACHMANIA; WINDA AYU SYAFITRI; DHIAN CHITRA AYU FITRIA SARI; SHUHEI YABE; AKIRA YOKOTA; ARIYANTI OETARI; Wellyzar Sjamsuridzal (Society for Indonesian Biodiversity, 2019)
Abstract. Setyaningsih PP, Ningsih F, Rachmania MK, Syafitri WA, Sari DCAF, Yabe S, Yokota A, Oetari A, Sjamsuridzal W. 2019. Cellulolytic enzyme-producing thermophilic Actinobacteria isolated from the soil of Cisolok Geysers, West Java, Indonesia. Biodiversitas 20: 3134-3141. This study investigated 17 thermophilic Actinobacteria isolated from the soil of geysers in the Cisolok geothermal area, West Java, as potential producers of cellulase. Screening for cellulase was performed on minimal (Mm) agar medium with and without the addition of 1% (w/v) carboxymethylcellulose (CMC) and microcrystalline cellulose (MCC), then incubated at 45, 50, 55 and 60°C for up to 7 days. Formation of clear zones around colonies indicated cellulose hydrolysis. The results showed that 15, 14, 4, and 3 isolates showed cellulolytic activity on CMC agar medium at 45, 50, 55, and 60°C, respectively, after 7 days of incubation. Three potential isolates showed cellulolytic activity on MCC agar medium after being incubated for 7 days at 45°C. Molecular identification based on the 16S rRNA gene was performed for three isolates with positive cellulolytic activity at 60°C. The results showed that the three isolates are closely related to Actinomadura keratinilytica WCC-2265T with 99.93-100% sequence similarities. A phylogenetic tree based on 16S rRNA gene sequences confirmed that the three isolates were clustered together with Actinomadura keratinilytica WCC-2265T with 100% bootstrap value. The tree also showed that cellulase producers and non-cellulase producers in Thermomonosporaceae are grouped into different clades.